Diet and proinflammatory cytokine levels in head and neck squamous cell carcinoma. Issue 17 (15th May 2014) - Arthur, Anna E.; Peterson, Karen E.; Shen, Jincheng; Djuric, Zora; Taylor, Jeremy M. G.; Hebert, James R.; Duffy, Sonia A.; Peterson, Lisa A.; Bellile, Emily L.; Whitfield, Joel R.; Chepeha, Douglas B.; Schipper, Matthew J.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Proinflammatory cytokine levels may be associated with cancer stage, recurrence, and survival. The objective of this study was to determine whether cytokine levels were associated with dietary patterns and fat‐soluble micronutrients in patients with previously untreated head and neck squamous cell carcinoma (HNSCC). METHODS This was a cross‐sectional study of 160 patients with newly diagnosed HNSCC who completed pretreatment food frequency questionnaires (FFQs) and health surveys. Dietary patterns were derived from FFQs using principal component analysis. Pretreatment serum levels of the proinflammatory cytokines interleukin‐6 (IL‐6), tumor necrosis factor alpha (TNF‐α), and interferon gamma (IFN‐γ) were measured using an enzyme‐linked immunosorbent assay, and serum carotenoid and tocopherol levels were measured by high‐performance liquid chromatography. Multivariable ordinal logistic regression models examined associations between cytokines and quartiles of reported and serum dietary variables. RESULTS Three dietary patterns emerged: whole foods, Western, and convenience foods. In multivariable analyses, higher whole foods pattern scores were significantly associated with lower levels of IL‐6, TNF‐α, and IFN‐γ (P ≤ .001, P = .008, and P = .03, respectively). Significant inverse associations were reported between IL‐6, TNF‐α, and IFN‐γ levels and quartiles of total reported carotenoid intake (P = .006, P = .04, and P = .04, respectively). There was an inverse association between IFN‐γ levels and serum α‐tocopherol levels (P = .03). CONCLUSIONS Consuming a pretreatment diet rich in vegetables, fruit, fish, poultry, and whole grains may be associated with lower proinflammatory cytokine levels in patients with HNSCC. Cancer 2014;120:2704–2712. © 2014 American Cancer Society.